Psychiatric Comorbidities in Non-psychogenic Chronic Itch, a US-based Study - Rachel Shireen Golpanian; Zoe Lipman; Kayla Fourzali; Emilie Fowler; Leigh A. Nattkemper; Yiong Huak Chan; Gil Yosipovitch (Medical Journals Sweden, 2020)
Research suggests that itch and psychiatric diseases are intimately related. In efforts to examine the prevalence of psychiatric diagnoses in patients with chronic itch not due to psychogenic causes, we conducted a retrospective chart review of 502 adult patients diagnosed with chronic itch in an outpatient dermatology clinic specializing in itch and assessed these patients for a co-existing psychiatric disease. Psychiatric disease was identified and recorded based on ICD-10 codes made at any point in time which were recorded in the patient's electronic medical chart, which includes all medical department visits at the University of Miami. Fifty-five out of 502 (10.9%) of patients were found to have a comorbid psychiatric diagnosis based on ICD-10 codes. The most common psychiatric diagnoses were anxiety disorders (45.5%), followed by major depressive disorder (36.4%). There was no significant association of any specific type of itch to a particular psychiatric disorder. No unique itch characteristics were noted in patients with underlying psychiatric diagnoses.